Synthesis and Analysis of the Density States and Optical Characteristics of Se100-X TeX Semiconductors - Wadi, Kassim M.; Hasan, Maher A.; Aneed, Shaymaa H.; Faraj, Mohammad G.; Jasim, Kareem A. (ARO-THE SCIENTIFIC JOURNAL OF KOYA UNIVERSITY, 2025)
The widespread commercial importance of selenium makes it an interesting element. It serves as an effective host matrix for chalcogenide alloys. However, pure selenium has a short lifetime and poor sensitivity. Therefore, specific chemical elements, such as tritium, have been used to overcome this problem. Se-Te alloys are preferred over selenium for their numerous advantages, such as increased electrical sensitivity, thermal stability, and applications in xerography. In this manuscript, the effects of partially substituting tellurium for selenium are studied for amorphous Se100-x Tex chalcogenide alloys prepared by melt quenching and spraying procedures to produce bulk and thin films, respectively, with varying tellurium concentrations (x = 10, 20, 30, and 40). X-ray diffraction of samples with different concentrations revealed that all samples had an amorphous (glassy) structure. Continuous electrical conductivity is also studied to determine the conduction mechanisms, effective energies, and densities of localized and extended states. The results of electrical conductivity measurements confirm the existence of two conduction modes (extended-state conduction at high temperatures and localized state conduction at intermediate and low temperatures in the tails of the conduction and valence bands). It is also found that the density of states, local and extended state coefficients, and activation energies are significantly affected by the partial substitution of selenium with tellurium. The optical properties of the Se₁₀₀₋ₓTeₓ films are studied using ultraviolet-visible spectroscopy, and it is found that the overall absorption increases while the energy gap decreases with increasing tellurium concentration.